Photocatalytic degradation of iron chelates fertilizers under UV light: a rapid evaluation for hydroponic growing systems - Alejandra Arcas; Silvia Valverde; Juan José Lucena; Sandra López-Rayo (Chemical and Biological Technologies in Agriculture)
Abstract Background Iron (Fe) deficiency in agricultural soils significantly affects crop productivity and quality. The application of synthetic Fe chelates is a common agricultural practice to address this issue, as they can maintain Fe solubility across a wide pH range. However, Fe chelates are susceptible to photodegradation, reducing their effectiveness, especially in hydroponic crops using UV radiation disinfection systems. This study aims to investigate the photodegradation behavior of six Fe chelates: classified as non-phenolic (EDTA, [S,S’]-EDDS, and IDHA) and phenolic (o,oEDDHA, HBED, and EDDHSA) agents, using a designed robust compact photocatalytic system with TiO2 under UV irradiation. The objective is to establish a straightforward and reliable methodology for predicting the photochemical behavior of Fe chelates in hydroponic cultivation systems. Results A Central Composite Design (CCD) was applied to establish the best experimental conditions. Kinetic parameters (order, rate constants and half-life) were determined in selected conditions, showing that both groups of chelates degrade differently under the conditions studied. In general, non-phenolic chelates showed faster degradation, while phenolic chelates, mainly o,oEDDHA/Fe3+ and EDDHSA/Fe3+, exhibited greater stability. The presence of macronutrients as well as copper slightly modified the photodegradation in a model nutrient solution, except for the chelate [S,S’]-EDDS/Fe3+, that is completely degraded. Despite TiO2 enhancing photodegradation, degradation rates are low enough in short times exposure to permit the reutilization of Fe chelates in recycled hydroponic systems. Conclusions The study demonstrates that the photodegradation rates of Fe chelates vary significantly between non-phenolic and phenolic agents, with the latter showing greater resistance to degradation under UV light in the TiO2-based photocatalytic system. The developed compact photocatalytic system has proven to be an effective tool for predicting the photochemical stability of Fe chelates, offering valuable insights for optimizing their use in soilless growing systems. Graphical Abstract